2019
DOI: 10.1007/s13361-019-02329-w
|View full text |Cite
|
Sign up to set email alerts
|

Protonated Clusters of Neon and Krypton

Abstract: We present a study of cationic and protonated clusters of neon and krypton. Recent studies using argon have shown that protonated rare gas clusters can have very different magic sizes than pure, cationic clusters. Here, we find that neon behaves similarly to argon, but that the cationic krypton is more similar to its protonated counterparts than the lighter rare gases are, sharing many of the same magic numbers. Electronic supplementary materialThe online version of this article (10.1007/s13361-019-02329-w) c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…This preserves the overall symmetry of the systems and explains why the protonated clusters better match models (which are often based on neutral clusters) [26]. A followup study on Ne and Kr clusters showed that the structural effect of protonation is strongest for lighter rare gases and decreases in strength for the heavier species [27]. It is therefore not expected to play a significant role for Xe clusters.…”
Section: Introductionmentioning
confidence: 80%
“…This preserves the overall symmetry of the systems and explains why the protonated clusters better match models (which are often based on neutral clusters) [26]. A followup study on Ne and Kr clusters showed that the structural effect of protonation is strongest for lighter rare gases and decreases in strength for the heavier species [27]. It is therefore not expected to play a significant role for Xe clusters.…”
Section: Introductionmentioning
confidence: 80%
“…The appearance of multiple distinct magic numbers for the protonated clusters mimics results with protonated rare gas clusters. 31,32 In the case of rare gases, the presence of a proton has a stabilizing effect on the clusters compared to pure, cationic systems. This leads to magic numbers for the protonated systems that match predictions for neutral rare gases and sphere packing models.…”
Section: Resultsmentioning
confidence: 99%
“…27,31 Here, the magic numbers for (N 2 ) n D + , most notably n = 2, 7, 12, and 17, match the packing of N 2 molecules around a (N 2 -D-N 2 ) + ionic core in icosahedral (sub-)shells, like was seen for the rare gases. 31,32 Calculated structures of (N 2 ) n H + clusters are shown in Figure 3 where the packing of increases. Our calculations indicate that the octahedral structure of (N 2 ) 6 H + is slightly favorable over (N 2 ) 7 H + with its pentagonal bipyrimid structure, which is consistent with the pair of magic numbers at these sizes found in the experimental data and their relative abundances.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations